Local Employment Impact of Growth Centres: Evidence from India - Kala Seetharam Sridhar (Urban Studies, Vol. 43, No. 12, 2205-2235, November 2006, 2006)
Evidence regarding non-tax incentives is sparse. To promote industrialisation in the backward areas of the country, growth centres providing infrastructure incentives to enable the states to attract industries, were set up by India in 1988. The impact of GCs on unemployment is examined, accounting for the simultaneity of GC status. The findings are that the change in population of a district and its growth potential are significant in determining actual GC status. The impact of demographic and socioeconomic factors on changes in a district's unemployment, is studied. The novel finding for a developing country is that it is not demand for labour, but the supply of labour, represented by population, that is the constraint in reducing the unemployment rate.